The Theological and Ethical Visual Dimensions of Pleasure and Suffering in the Grave in the Perspective of the Prophet's Hadith - Fitriyani, Dina; Al Ayubi, Sholahuddin; Alif, Muhammad (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2025)
The grave realm is often also called the supernatural realm. The grave is described as an intermediary between the day of death and the day of resurrection. Many people are asking about what life is like after being in the world. They are worried about their fate after the last breath, the grave becomes a mystery that makes us want to know what the conditions of life are after being in the world. In the Islamic tradition, life after death is an important aspect of faith. It is believed that the grave is a transitional period before Judgment Day, where people experience joy and suffering based on their deeds in this life. The Prophet's hadith discusses a lot about the reality of life in the grave and provides an overview of the spiritual condition of human beings after death. The theological and ethical aspects of the pleasures and sufferings of the grave are topics that are often discussed in Islamic studies, although some aspects still need further clarification. Although there is a lot of research on the afterlife, there is still a lack of explaining how the pleasures and sufferings of the grave realm are from the perspective of prophetic tradition, especially from a theological and ethical perspective. In addition, there is no clear mapping of how these dimensions affect the daily moral life of Muslims. The purpose of this study is to analyze in depth the theological and ethical aspects of pleasure and suffering in the grave based on the hadiths of the Prophets. This research will explore how these hadiths describe the theological conception of life after death and its moral implications for Muslims in this life. Thus, this research is expected to deepen our understanding of the role of pleasure and suffering in the grave in shaping the ethical behavior of Muslims.